Firm size sensitivity on the correlation between financing choice and firm value - Yossi Diantimala; Sofyan Syahnur; Ratna Mulyany; Faisal Faisal (Cogent Business & Management, 2021)
This study examines the impact of firm size on the effect of capital structure choice on the firm value in one of the emerging markets, Indonesia. The study of capital structure choice and firm value in emerging markets is captivating due to the different characteristics of its companies as compared to the characteristics of companies in developed countries. To rigorously conduct the research, this study uses annual reports and market value of 1,638 listed non-financial companies as the result of a random sampling method with 7-year observation periods, 2012 until 2018. The finding supports the existing literature that optimal capital structure choice reflects an appropriate mix of debt and the company's equity that enhances the firm value. This means that capital structure is one of the significant aspects of the decision-making of investment by investors. Similar to that in developing countries, increasing long-term debt is a funding option when the internal funds are insufficient. Reducing retained earnings affected by lower profitability level increase corporate long-term debt. Furthermore, the size of a company takes an important role to strengthen the impact of capital structure choice on the firm value.
Keywords: G32; 650; Capital structure; firm value; emerging market firm; profitability